Radioembolization of Secondary Hepatic Malignancies - Manchec, Barbara; Kokabi, Nima; Narayanan, Govindarajan; Niekamp, Andrew; Peña, Constantino; Powell, Alex; Schiro, Brian; Gandhi, Ripal (Seminars in Interventional Radiology, 2021)
Cancer has become the leading cause of mortality in America, and the majority of patients eventually develop hepatic metastasis. As liver metastases are frequently unresectable, the value of liver-directed therapies, such as transarterial radioembolization (TARE), has become increasingly recognized as an integral component of patient management. Outcomes after radioembolization of hepatic malignancies vary not only by location of primary malignancy but also by tumor histopathology. This article reviews the outcomes of TARE for the treatment of metastatic colorectal cancer, metastatic breast cancer, and metastatic neuroendocrine tumors, as well as special considerations when treating metastatic disease with TARE.
Keywords: radioembolization; hepatic metastasis; liver-directed therapies